Performance of traditional household drinking water treatment methods used in rural Amazon - Gomes, Maria Cecilia Rosinski Lima; de Andrade, Leonardo Capeleto; Barbosa, Milena Pinho; Lopes, Bruna Coelho; Mota Filho, Cesar Rossas (Frontiers in Water, 2024)
Residents of remote areas in the Amazon often lack access to a water supply system and thus need to produce their potable water at home. This study examined the efficacy of household water treatments traditionally used by these communities to treat rainwater and river water, their predominant water sources. Samples of untreated, treated, and stored drinking water were collected from 18 households in three communities in Central Amazon, Amazonas State, Brazil. We describe the materials and practices involved and traditionally used in each treatment technique – cloth filtration (water straining), chlorination, and sedimentation, and their efficiency. In the samples we evaluate water quality analyses, as free chlorine, color, coliforms, and turbidity. The treatment steps for the separation of solids in river water were effective only for removing turbidity and apparent color. Straining river water after sedimentation had no relevant effect on water quality. Chlorination of rainwater was efficient in inactivating Escherichia coli; however, all samples showed some level of contamination by E. coli. We found a significant difference (p < 0.05) between untreated and treated river water turbidity, reduced by up to 22%. Untreated rain and river waters showed similar levels of microbiological contamination, close to 3.5 log CFU/100 mL of E. coli. Chlorine effectively removed microbiological contaminants in rainwater (median removal of 100, 44.5% of samples with <1 CFU/100 mL). Yet, this treatment was less effective for river water (94% median removal, with 11% of samples with <100 CFU/100 mL and only 5.5% with <1 CFU/100 mL found in treated water), showing a significant reduction in both cases when the Wilcoxon test was applied. Sodium hypochlorite treatment showed the best results among the techniques evaluated in this study. It can be used in remote areas where rainwater is available for consumption. Microorganism concentration increased after water underwent water straining and sedimentation processes. These results suggest that the improper handling of water containers and materials used during treatment processes leads to contamination of water. Thus, more robust outreach and educational efforts are recommended to improve remote communities’ water collection, treatment, and storage practices.